2014
DOI: 10.1007/s10517-014-2665-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Proinflammatory Cytokine Levels and Their Role in the Development of Local and Systemic Effects during Progressing Cervical Cancer

Abstract: In order to evaluate the role of cytokines in the development of polymodal local and distant effects in patients with stages I-IV cervical cancer, the following parameters were measured: serum concentrations of TNF-α, IFN-γ, IL-1β, IL-6, and IL-10; levels of malondialdehyde, activities of catalase, superoxide dismutase, glutathione reductase, and glutathione-S-reductase in the plasma, erythrocyte, and cervix uteri homogenate. The expression of p53, Bcl-2, VEGF, and Ki-67 in tumor tissue was evaluated. High lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In recent years, authors say that marking IL-6 concentrations before treatment can influence the estimation of DFS and OS. They place stress on the important role of proinflammatory cytokines, IL-6 included, in the progression of cervical cancer, particularly in early stages of development [ 5 , 27 ]. Our studies confirmed those reports.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, authors say that marking IL-6 concentrations before treatment can influence the estimation of DFS and OS. They place stress on the important role of proinflammatory cytokines, IL-6 included, in the progression of cervical cancer, particularly in early stages of development [ 5 , 27 ]. Our studies confirmed those reports.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found a correlation between HPV infection and serum IL-10 levels in local tissue [ 19 ]. In fact, two studies found an increase in serum IL-10 associated with various stages of cervical cancer [ 20 , 21 ]. Moreover, immature stromal dendritic cells expressing IL-10 are more numerous in cervical cancer than in normal cervix and cervical intraepithelial neoplasia [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Followed by production of chemokines, vascular growth factor and tumor growth factor provide favorable immune microenvironment for the survival of tumor cells and progression of lesion. Additionally, the circulating levels of TNF-α were increased with the increased clinical stage progress, and expression levels of KI-67, Bcl-2 and p53 in stage Iβ-IIa of cervical carcinoma were positively correlated with the levels of TNF-α [17].…”
Section: Discussionmentioning
confidence: 94%